Modelagem Fenomenológica do Escoamento de Fluido de Perfuração em Peneiras Vibratórias - Pereira, Monique Cristina Viana (2017)
Drilling fluids are substances injected into the well whose main function is to suspend drilled solids, remove them from the well bore and release them at the surface. Separation and reuse of drilling fluids is of great importance to fulfill the requirements of environmental legislation regarding waste disposal. In addition, it is essential to recover the drilling fluid in order to reduce costs of the drilling process. The objective of the present study was to develop a mathematical model based on the principles of Newtonian dynamics and the law of mass conservation for the process of removal of drilled cuttings from drilling fluid using vibrating screens. For this purpose, the sieve screen was considered to be a very thin packed bed and tilted upward. Pressure drop correlations were analyzed and a new correlation was proposed based on methodologies indicated in the literature. The behavior of the fluid was evaluated for the variation in the following parameters: plastic viscosity, yield stress, flow coefficient, tilt of the screen and g factor. The model was not sensitive to variations in the yield stress of the fluid while other parameters showed a significant influence on wet screen length. Obtained results are in agreement with the reported ones in the literature and show that the developed model is suitable for the description of the process of vibrating screening.